Inhibition of Herpes Simplex Virus Type 1 by Thymol-Related Monoterpenoids - Lai, Wen-Lin; Chuang, He-Shing; Lee, Meng-Hwan; Wei, Chia-Li; Lin, Chin-Fu; Tsai, Ying-Chieh (Planta Medica, 2012)
This study examined the anti-herpes simplex virus type I activity of the major constituents of several essential oils. Plaque reduction assays were performed to evaluate anti-herpes simplex virus type I activity. Thymol and carvacrol both possessed significant antiviral activity with an IC50 of 7 µM, and herpes simplex virus type I was 90 % inactivated within 1 hr. The mode of antiviral action was shown to affect the virion directly. Evidence was also observed by electron microscopy. Evaluation of the structural requirements for antiviral activity of thymol-related monoterpenoids revealed that aliphatic side chains had a minor effect, while a hydrophilic group on the benzene ring was sufficient for activity. Our results suggest that thymol and carvacrol are potential candidates for topical therapeutic application to reduce herpes simplex virus transmission.
Keywords: monoterpenoids; antiviral; herpes simplex virus type 1; thymol; carvacrol